Repairing work of waterproofing (Kementerian Kewangan, Putrajaya) / Siti Nor Juanna Hamidon - Hamidon, Siti Nor Juanna (2014)
Public Works Department (PWD) of Malaysia was established since 1872 and serves as a technical agency of the Government of Malaysia. PWD is responsible for performing development projects and infrastructure maintenance to various ministries, departments, statutory bodies and state governments such as roads, buildings, airports, ports and jetties.